(untitled) (Journal of Nepal Geological Society, 2015)
Landslides are very common occurrences in Nepal that have been affected development infrastructures, lives, and properties of the people every year. Many hill villages are situated on or adjacent to unstable slopes and old landslides are reactivated from time to time. The rapidly increasing construction of infrastructure, such as roads, irrigation canals, and dams without due consideration of natural hazards is contributing to triggering of landslides and debris flows. Thus, this paper has explored the cause and characteristics of landslides occurrences and their mitigation practices in Nepal. Topographic, geologic and triggering factors, and human intervention causing landslides are characterised to suggest the suitable mitigation options that can be implemented in the mountain hill-slopes. Among the wide range of slope stabilisation measures which are available to practitioner engineer, the lowering of groundwater level in combination of controlling of surface infiltration (e.g. sealing of tension cracks) of water into landslide are the most cost effective options for mountainous terrain because the rise in pore water pressure is one of the basic cause of landslides during the rainy season. In addition, removing of unstable slope debris, surface drainage, and retaining walls are the useful landslide mitigation measures depending on site conditions, availability of budget, and specific requirements. Various support systems and elements can be crafted for creative solutions of the slope instability problems in Nepal.